Significance of climate change in the emergence of human fascioliasis in Upper Egypt - Naglaa Zanaty; Nagat Ibrahim; Haidi Karam-Allah Ramadan; Alzahraa Abdelraouf Ahmad; Amal Saad-Hussein (Tropical Diseases, Travel Medicine and Vaccines)
Abstract Background Climate change in the upcoming years will raise the health burden of zoonotic parasites. As a liver fluke, Fasciola depends on certain climate conditions to complete its life cycle and is significantly influenced by climate changes. We aimed to investigate the relationship between the increasing prevalence of human fascioliasis and climate changes in Upper Egypt. Methods Records of Fasciola cases in Assiut Governorate in Upper Egypt were evaluated between September 2018 and March 2023. The annual and monthly climate parameters of the region’s temperature and humidity acquired from ERA5 and FLDAS were investigated between 2000 and 2023. Results A total of 303 patients were included. The mean age was 33.9 ± 17.4 years; 57.1% were females, and the majority were rural residents. Positive correlations were found between temperature and the recorded cases in 2018, 2020, 2021, and 2022 (r = 0.92, 0.41, 0.61, and 0.60, respectively). In 2018 and 2022, humidity and Fasciola frequency had a significant positive correlation (r = 0.97 and 0.49, respectively). An outbreak of fascioliasis was recorded in September 2018, coinciding with the peak temperature and high humidity levels, exceeding the average climatology range from 2000 to 2017. The recorded cases exhibited a seasonal pattern, with peaks in hot, humid summer and autumn. Conclusion The rise of human fascioliasis in Upper Egypt is influenced by local climate characteristics. A climate-based map of Fasciola distribution using forecast risk models is needed to predict future outbreaks and for better control.